Research Progress of Macropinocytosis in Digestive System Tumors - CHEN Ting; YAN Shuguang; LI Jingtao; WEI Hailiang; ZHOU Yongxue (Zhongliu Fangzhi Yanjiu, 2023)
Macropinocytosis, an evolutionarily conserved, actin-dependent form of endocytosis, is involved in various physiological processes, including nutrient absorption, antigen presentation, and cell signaling transduction and migration. Oncogene activation and tumor suppressor inactivation induce macropinocytosis in tumors in the digestive system, involved in tumorigenesis and progression, whereas the inhibition of macropinocytosis slows the aggressive phenotype of digestive system tumors and improves the efficacy of anti-tumor drugs. Macropinocytosis can also be used as a delivery route for anti-tumor drugs. Therefore, macropinocytosis has been widely studied to develop new methods for the treatment of digestive system tumors.This paper reviews the role of macropinocytosis in the body, the regulation of macropinocytosis-related signaling pathway, as well as the mechanism of macropinocytosis in colorectal cancer, pancreatic ductal adenocarcinoma, liver cancer and other digestive system tumors, to provide reference for related researches.